2022
DOI: 10.1186/s12974-022-02611-x
|View full text |Cite
|
Sign up to set email alerts
|

T-cells in human trigeminal ganglia express canonical tissue-resident memory T-cell markers

Abstract: Background Trigeminal ganglia (TG) neurons are the main site of lifelong latent herpes simplex virus type 1 (HSV-1) infection. T-cells in ganglia contribute to long-term control of latent HSV-1 infection, but it is unclear whether these cells are bona fide tissue-resident memory T-cells (TRM). We optimized the processing of human post-mortem nervous tissue to accurately phenotype T-cells in human TG ex vivo and in situ. Methods Peripheral blood mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Resident T cells have also been observed in sensory ganglia ( 45 , 46 ) and are more prominent during latent viral infections ( 47 , 48 ). We thus asked whether residency markers associated with T cells in other tissues were also observed in the DRG or TG.…”
Section: Resultsmentioning
confidence: 99%
“…Resident T cells have also been observed in sensory ganglia ( 45 , 46 ) and are more prominent during latent viral infections ( 47 , 48 ). We thus asked whether residency markers associated with T cells in other tissues were also observed in the DRG or TG.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies in humans and mice have shown that T-cells, mainly CD8 T-cells, control HSV not only at the site of lytic infection (e.g., in the skin and mucosa) but also at the site of latency in ganglia [ 10 , 12 , 13 ]. At both of these peripheral sites, virus-specific T-cells are retained as tissue-resident memory T-cells (T RM ) to control HSV reactivation [ 13 , 14 ]. Although analogous infiltration and retention of virus-specific T RM has been observed in the skin of VZV-infected individuals [ 15 , 16 ], prior studies using only a small number of VZV proteins failed to detect VZV reactive T-cells in human TG [ 17 ].…”
Section: Introductionmentioning
confidence: 99%